Solve:
![\frac{x - 3}{5} + \frac{x - 4}{7} = 6 - \frac{2x - 1}{35} \frac{x - 3}{5} + \frac{x - 4}{7} = 6 - \frac{2x - 1}{35}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx+-+3%7D%7B5%7D++%2B++%5Cfrac%7Bx+-+4%7D%7B7%7D++%3D+6+-++%5Cfrac%7B2x+-+1%7D%7B35%7D+)
Answers
Answered by
4
Therefore, multiplying both sides of the equation by 35.
Answered by
0
Solutions:
(x + 3 /5) = (x - 4 /7) = 6 - (2x - 2 /35)
L.C.M of 5,7 and 35 = 35
Therefore, multiplying both sides of the equation by 35.
35 × (x + 3 /5) + 35 × (x - 4 /7) = 35 × 6 - (2x - 2 /35)
7(x - 3) + 5(x - 4) = 210 - (2x - 1)
7x - 21 + 5x - 20 = 210 + 2x + 1
7x + 5x - 21 - 20 = 210 + 1 - 2x
12x + 2x = 211 + 2x
14x = 252
x = 18
silentlover45.❤️
Similar questions